Decreased Blood Levels of Oxytocin in Ketamine-Dependent Patients During Early Abstinence - Huang, Ming-Chyi; Chen, Lian-Yu; Chang, Hu-Ming; Liang, Xiao-Yu; Chen, Chih-Ken; Cheng, Wan-Ju; Xu, Ke (Frontiers in Psychiatry, 2018)
Background: Ketamine, an N-methyl-D-aspartate (NMDA) eceptor antagonist, is a common drug of abuse worldwide. Existing evidence suggest a disruption of oxytocin system involves in the development of addiction-. In this study, we aimed to investigate the role of oxytocin in ketamine addiction by measuring the blood oxytocin levels in ketamine-dependent (KD) patients. Methods: Sixty-five KD patients and 65 controls were enrolled. Fasting plasma levels of oxytocin were determined at baseline and 1 and 2 weeks after ketamine withdrawal. Ketamine use variables, Beck Depression Inventory, Beck Anxiety Inventory (BAI), Visual Analogue Scale for craving, and Childhood Trauma Questionnaire-short from were assessed in KD patients. Results: KD patients had significantly lower levels of oxytocin at baseline compared to controls (9.53 ± 4.17 vs 5.89 ± 2.13 ng/mL, P < 0.001). Oxytocin levels increased after one (6.74 ± 2.63, P < 0.002) and two weeks (6.89 ± 2.69, P = 0.01) of withdrawal in KD patient despite the levels were still lower than controls (P = 0.001 and 0.002 respectively). The clinical variables did not correlate with baseline oxytocin levels except BAI scores, which showed a negative correlation with the levels (r = -0.263; P=0.039). Conclusion: We found a distinctively reduced oxytocin level in KD patients and the level did not normalize after early abstinence. Lower oxytocin might be associated with anxious phenotype of ketamine addiction. These results suggest that oxytocin system dysregulated following chronic ketamine abuse and might provide insight in evaluating the potential therapeutic use of oxytocin for treating ketamine addiction.